Motor coordination and weight status in children according to area of residence - Živan Milošević; Filip Sadri; Ivo Sadri; Marijana Sinđić; Maja Batez (Exercise and Quality of Life)
A good understanding of potential differences in motor coordination and weight status in children from rural and urban areas may advance targeted measures implemented by experts in the field of sports and physical education. This research study is focused on investigating differences in the total motor coordination score and weight status in 70 children aged (7 to 8) living in different residential areas within the territory of the city of Šabac, Republic of Serbia (35 urban and 35 rural areas). The Körperkoordinations Test für Kinder battery of tests was used for the assessment of the overall motor coordination. By application of t-test for independent samples, the obtained results indicate that there are statistically significant differences in the majority of the applied motor tests (walking backward, p=0.000; hop for height on one leg, p=0.033; side jumps, p=0.002), as well as in the total motor coordination scores (p=0.000) in favor of the children from rural environments. The weight status of children indicates no statistically significant differences between the two groups (p=0.376).